Violence against women: knowledge and preparation of primary health care professionals in a municipality in southeastern Pará (Research, Society and Development, 2021)
This study aimed to quantify and qualify the knowledge of health professionals in approaching women victims of any type of aggression, in a municipality with high rates of violence against this gender in southeastern Pará. descriptive, analytical and cross-sectional nature, with a quantitative approach, carried out through an online questionnaire applied to physicians, nurses and nursing technicians in primary care in the city of Marabá-PA, the questionnaire consisted of questions about socioeconomic aspects, opinion questions about Violence Against Women (VCM), on the management of confirmed cases of VAW, on the management of suspected cases of VAW and questions about the difficulties of health professionals. 51 responses were obtained, 8 from doctors, 15 from nurses and 28 from nursing technicians, where 68% were women. Of the total, 76.4% have already assisted victims of domestic violence, 70.5% think that the laws partially protect women, 64.7% think that women are not treated the same as men, most have inappropriate behavior regarding the approach of victims in relation to medications and psychotherapy, with inappropriate conduct being their main personal difficulty and weakness in the application of laws as a structural difficulty. It is noticed that health professionals in primary care in a municipality in the southeast of Pará have limited knowledge and preparation on the management of women victims of violence and misunderstanding about some conducts.